SIRT1 improves endothelial function by suppressing oxidative stress in diabetic mice. (14th October 2021) - Yang, K; Velagapudi, S; Camici, G; Xu, A; Luescher, T F
Abstract: Background: The activation of longevity gene and the intracellular expression of the protein SIRT1 in vivo shows beneficial effects in different organs including cardiovascular function [1]. However, it is not known whether extracellular SIRT1 plays a role and has favorable effects on endothelial and vascular function. Purpose: The current study aimed to investigate the effects of in-vivo treatment of diabetic mice with recombinant mouse SIRT1 (rcSIRT1) on endothelial and vascular dysfunctions. Methods: Db/db mice of 12 weeks of age and their lean controls were treated with vehicle or rcSIRT1 protein intraperitoneally for 4 weeks with a dose of 5μg/mouse /day. At the end of the treatment period, pulse wave velocity of carotid arteries was examined with echocardiology and the activities of mouse were recorded through metabolic cage housing system. Aorta, carotid arteries, and mesenteric arteries were isolated at sacrifice to assess endothelial and vascular function in myograph systems. Results: The db/db mice treated with rcSIRT1 were more active in the dark cycle. Their vascular functions were improved as aortas exhibited reduced contractions to phenylephrine and increased relaxations to acetylcholine. Carotid arteries also performed better function as the pulse wave velocity was reduced and endothelium-dependent contracting factors were significantly decreased after treatment. Mesenteric resistance arteries had preserved endothelial dependent hyperpolarization compared to the controls. Incubation with different inhibitors showed that rcSIRT1 exerted beneficial effects on vascular function by supressing oxidative stress which were mediated by NADPH oxidase and COX-1 pathways. Conclusions: Exogenous treatment of diabetic mice with recombinant SIRT1 significantly improves endothelial and vascular function. Circulating Sirt1 may be a novel therapeutic preventing diabetic vascular disease. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Swiss National Science Foundation